FeSe2 nanosheets as a bifunctional platform for synergistic tumor therapy reinforced by NIR-II light. (13th July 2021) - Fang, Lan; Wang, Jie; Ouyang, Xueliang; Liang, Binbin; Zhao, Liying; Huang, Dechun; Deng, Dawei
Abstract : FeSe2 nanosheets, relying on their inherent NIR-II-mediated photothermal property and photothermal-enhanced photodynamic performance, provide a new paradigm for the design of advanced drug carriers. Abstract : Multi-functionality has been a constant pursuit in the development of next-generation drug carriers, as it will bring the potential for combination therapy by integrating diverse therapeutic modes. In this work, FeSe2 nanosheets (NSs) have been prepared as a bifunctional platform to investigate their use in synergistic cancer therapy. Bifunctional FeSe2 NSs exhibit exceptional Fenton-like activity that generates cytotoxic hydroxyl radical (˙OH) and strong broad photothermal performance including the second-infrared (NIR-II) spectral range, wherein the ˙OH production can be enhanced by NIR-II light irradiation. Furthermore, doxorubicin (DOX) was conjugated onto NSs via a pH-responsive hydrazone bond to achieve preferential drug release in an acidic microenvironment. Upon intratumoral administration, these bifunctional drug-carrying FeSe2 NSs showed an NIR-II irradiation-reinforced strong tumor suppression effect, and no obvious toxicity to normal tissues was observed. This study provides a new paradigm for the design of advanced drug carriers relying on their inherent physicochemical properties.